Topics in geometry, coding theory and cryptography - Garcia Arnaldo; Stichtenoth Henning (Dordrecht Springer-Verlag, 2007)
This book presents survey articles on some of these new developments. Most of the material is directly related to the interaction between function fields and their various applications; in particular the structure and the number of rational places of func
Keywords: Coding theory; Cryptography; Geometry